EPC infusion ameliorates acute graft-versus-host disease-related endothelial injury after allogeneic bone marrow transplantation - Wang, Weiwei; Ye, Yali; Du, Yuwei; Xu, Zhengqing; Yuan, Ke; Wang, Yizhou; Adzraku, Seyram Yao; Li, Yue; Xu, Kailin; Qiao, Jianlin; Ju, Wen; Zeng, Lingyu (Frontiers in Immunology, 2022)
Graft-versus-host disease (GVHD) damages vascular endothelium. Endothelial progenitor cell (EPC) can differentiate to endothelial cell and promote angiogenesis, but its role in endothelial damage in GVHD is unclear. In this study, we intend to assess whether EPC infusion promotes the repair of endothelial injury in GVHD mouse model. Male BALB/c mice were randomly divided into 5 groups: control group, total body irradiation group (TBI group), allogeneic bone marrow transplantation group (Allo-BMT group), acute graft versus host disease group (GVHD group), EPC infusion group (GVHD+EPC group) followed by analysis of mice survival, acute GVHD (aGVHD) score, T cell infiltration by immunofluorescence, as well as continuity of vascular endothelium in liver. Compared with Allo-BMT group, the clinical and pathological score of aGVHD mice were higher. On day 21 after transplantation, a large number of mononuclear cell infiltrations were seen in the target tissues of aGVHD mice and mice died within 30 days. In addition, aGVHD group also presented increased subendothelial infiltration of CD3+ T cells in the liver, decreased VE-cadherin expression and elevated major histocompatibility complex (MHC) II molecule expression in the endothelium. Moreover, expression of MHC-II molecule increased in endothelial cell after irradiation injury and LPS stimulation, indicating abnormally activated endothelial cell with antigen-presenting function. Interestingly, infusion of EPC reduced the clinical and pathological score of aGVHD, decreased infiltration of mononuclear cells, improved survival as well as upregulated VE-cadherin and downregulated MHC-II molecule. In conclusion, EPC infusion can mobilize to affected endothelium to decrease the infiltration of T cells and pathological endothelial activation contributing to ameliorating the damage of endothelium. EPC infusion combined with bone marrow transplantation might be a perspective strategy for the prevention and treatment of aGVHD.